Improving Balanced Nutrition Knowledge among Mothers of Toddlers through Education and Menu Demonstration at Posyandu - Utami; Santi Aprilian Lestaluhu; Renita Afriza (CV. Get Press Indonesia, 2025)
To evaluate the effectiveness of educational interventions and demonstrations of balanced nutrition menus on increasing the knowledge of mothers of toddlers. This study used a quantitative approach with a pre-experimental design of one group pretest-posttest design. The participants were mothers who had children aged 0-5 years and actively participated in Posyandu activities in the local Puskesmas work area. Before and after the intervention, the level of knowledge of respondents was measured using a validated questionnaire instrument, containing 20 multiple-choice questions about the concept of balanced nutritional, types of food, balanced portions, and toddler food processing techniques. The results of the inferential analysis using the paired sample t-test showed that there was a significant difference between the pretest and posttest scores (p < 0.05). Community-based nutrition education programs accompanied by direct demonstrations are highly recommended as a strategy to increase community nutrition literacy, especially in efforts to prevent toddler nutrition problems such as stunting and malnutrition.